Using Dafny, an Automatic Program Veri er - Herbert, Luke; Leino, Rustan; Quaresma, Jose (Tools for Practical Software Verification, 2012)
These lecture notes present Dafny, an automated program verification system that is based on the concept of dynamic frames and is capable of producing .NET executables. These notes overview the basic design, Dafny's history, and summarizes the environment configuration. The key language constructs, and various system limits, are illustrated through the development of a simple Dafny program. Further examples, linked to online demonstrations, illustrate Dafny's approach to loop in-variants, termination, data abstraction, and heap-related specifications.